Given: f(x) = 4x^2 + 4x - 2

First find the prime factors for each term on the right side of the equation:

4x^2 = 2*2*x*x

4x = 2*2*x

2 = 2

The greatest common factor (GCF) = 2

Next, factor out the GCF:

4x^2 + 4x - 2 = 2(2x^2) + 2(2x) + 2(-1)

= 2(2x^2 +2x - 1)

Your answer is:

f(x) = 2(2x^2 + 2x - 1)

All the best,

Dinshaw

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up